2023
DOI: 10.1038/s41467-023-39841-3
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric solitons crafted in epitaxial bismuth ferrite superlattices

Abstract: In ferroelectrics, complex interactions among various degrees of freedom enable the condensation of topologically protected polarization textures. Known as ferroelectric solitons, these particle-like structures represent a new class of materials with promise for beyond-CMOS technologies due to their ultrafine size and sensitivity to external stimuli. Such polarization textures have scarcely been demonstrated in multiferroics. Here, we present evidence for ferroelectric solitons in (BiFeO3)/(SrTiO3) superlattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These inclusions, which are coherent with the matrix, were intentionally randomly dispersed throughout the BFO phase by careful control of the thin film deposition conditions. Such designer defect inclusions not only help to maintain the high crystalline quality of the T’ BFO phase but also enable an almost perfectly reversible phase transformation between T’ and R’ BFO using a local applied electric field as well as the longest reported nanoscale domain stability in a thin film ferroelectric system. , More recently, we have shown that they can assist in the formation of ferroelectric solitons in superlattices of BFO-SrTiO 3 (STO) and influence the temperature-dependent spin Hall magnetoresistance of epitaxial BFO . Note that the stabilization of T’ BFO by BO phases is not restricted to growth on LAO substrates alone.…”
Section: Introductionmentioning
confidence: 99%
“…These inclusions, which are coherent with the matrix, were intentionally randomly dispersed throughout the BFO phase by careful control of the thin film deposition conditions. Such designer defect inclusions not only help to maintain the high crystalline quality of the T’ BFO phase but also enable an almost perfectly reversible phase transformation between T’ and R’ BFO using a local applied electric field as well as the longest reported nanoscale domain stability in a thin film ferroelectric system. , More recently, we have shown that they can assist in the formation of ferroelectric solitons in superlattices of BFO-SrTiO 3 (STO) and influence the temperature-dependent spin Hall magnetoresistance of epitaxial BFO . Note that the stabilization of T’ BFO by BO phases is not restricted to growth on LAO substrates alone.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study of using magnetic fields in superlattices can be seen as a possible way to design and generate new optical devices for future all-optical technologies. Recently, even the influence of randomness has been studied in similar optical devices [12], and nonlinear modes such as ferroelectric solitons in epitaxial bismuth ferrite superlattices have been successfully observed in experimental setups [13]. In a standard approach, it is assumed that such an external magnetic field points in one constant direction, and then one studies how the strength of this field affects the way that light behaves in the superlattice system.…”
Section: Introductionmentioning
confidence: 99%